Desarrollo de un sistema de gestión de riesgos bajo la norma iso 31000-2009, en la industria “INDUACERO”. - Armas Hernández, Mitchel Samuel (2019)
The purpose of this research project is to develop a risk management system under ISO 31000-2009 standard in "INDUACERO" company for organizational improvement through the identification, analysis and evaluation of these, in order to provide a higher level of competitiveness to the organization, in addition to the comfort and the fulfillment of organization´s objectives. The ISO 31000 standard is fundamental to complement the processes of risk management in strategic processes, planning, management, reporting and provides certain guidelines for the implementation of an organizational culture. Organizational risks are a problem that are always present within any organization, and if they are not treated in time, they can have negative effects on the company objectives, the risks can also affect the processes, human, physical, technological, financial and organizational resources. The methodology to be used for the application of ISO 31000 standard, is composed of four phases, the first is to establish the organization context, the second one is the risks assessment, the third one is to establish instruments for risk management and finally, to design monitoring mechanisms for risk management; In order to guarantee the continuity of the operations and the goals achievement, "INDUACERO" needs to control the effects caused by these risks. With the elaboration of this research project it is desired that the company INDUACERO can avoid or diminish in its great majority the organizational risks that the company has such as corporate image, human talent and operational risk, who represent the highest value in the Risks evaluation. As a final result, the risk matrix was obtained, which allows knowing the deficient factors and proposing corrective actions to guarantee an efficient and effective development of the company.